2007
DOI: 10.1177/1073858407305725
|View full text |Cite
|
Sign up to set email alerts
|

TNF α: A Trigger of Autonomic Dysfunction

Abstract: During disease, infection, or trauma, the cytokine tumor necrosis factor α (TNF α ) causes fever, fatigue, malaise, allodynia, anorexia, gastric stasis associated with nausea, and emesis via interactions with the central nervous system. Our studies have focused on how TNF α produces a profound gastric stasis by acting on vago-vagal reflex circuits in the brainstem. Sensory elements of this circuit (i.e., nucleus of the solitary tract [NST] and area postrema) are activated by TNF α . In response, the efferent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 74 publications
2
41
0
1
Order By: Relevance
“…Increased IL-1b production and macrophage activity in the brain correlate with the fatigue associated with recovery from muscle damage (71). TNFa elicits malaise, characteristic of brain inflammatory disorders (72), and strongly impacts on various autonomic functions (73,74). Lacosta and others (75) showed that chronic systemic administration of IL-2 in mice reduces exploration and spatial working memory.…”
Section: Resultsmentioning
confidence: 97%
“…Increased IL-1b production and macrophage activity in the brain correlate with the fatigue associated with recovery from muscle damage (71). TNFa elicits malaise, characteristic of brain inflammatory disorders (72), and strongly impacts on various autonomic functions (73,74). Lacosta and others (75) showed that chronic systemic administration of IL-2 in mice reduces exploration and spatial working memory.…”
Section: Resultsmentioning
confidence: 97%
“…The expression of peripheral cytokines, including TNF-α, mediates the malaise observed in central nervous system inflammatory disorders [23]. TNF-α can cause aberrations in various central and systemic autonomic functions [41,42,43]. Neopterin may activate ONS pathways [44,45,46] and cell-signaling networks that are involved in both disorders [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…In ME/CFS there is substantial evidence of increased ONS, oxidative damage to membrane fatty acids and DNA, and nitrosative damage to proteins [11,12,19]. PICs, such as IL-1 and TNF-α, elicit FS symptoms, such as fatigue, malaise, hyperalgesia and autonomic symptoms [20,21,22,23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…Anti-TNF antibodies (infliximab, etanercept) are the popular drugs in IBD (9) to curb the increased TNF levels during inflammation (10). Increased TNF levels has been demonstrated to increase epithelial permeability (11), induce neuropathic pain (12) and colonic motility dysfunctions (13, 14). In the present study we investigated if TNF induces NPY expression during inflammation in the ENS, and whether NPY-TNF interactions can regulate inflammation, epithelial permeability and colonic motility.…”
Section: Introductionmentioning
confidence: 99%